Dynamics of Family Roles in Business Decision Making: A Case Study at Teras Herritage Café, Malang (ePaper Bisnis : International Journal of Entrepreneurship and Management, 2025)
This study aims to describe the dynamics of family business management at Teras Herritage Café in Malang City by highlighting role division, communication patterns, business operations, challenges, and the relationship between family and non-family employees. Using a qualitative approach with a case study strategy, data were collected through semi-structured interviews with the owner, family members, and non-family employees, as well as direct observation at the business location. The results show that café management is strongly influenced by family values, particularly the principle of mutual cooperation and role flexibility that allows all family members to be actively involved in operations. Although differences of opinion often arise, they are resolved through open communication, preventing significant conflict. The main challenges of the business include limited digital marketing, location competition, and suboptimal technical facilities. The relationship between family and non-family employees is harmonious, characterized by fair treatment and an inclusive work environment. The study's conclusions confirm that family social capital is a key strength in maintaining business stability, but strengthening the management structure, marketing strategy, and long-term planning is needed for the business to grow sustainably.